2018
DOI: 10.5539/jas.v10n9p389
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Genes Associated With Degradation Enhancement of Imazethapyr in Barnyardgrass (Echinochloa crus-galli)

Abstract: The understanding of mechanism of herbicide resistance in weeds is essential for adequate or innovative weed management practices. The aim of this study was to identify and analyze the expression of genes related to degradation enhancement of imazethapyr in barnyardgrass (Echinochloa crus-galli L. Beauv.). One susceptible (SUSSP01) and two populations previouslly identified as resistant to imazethapyr (ARRGR01 and PALMS01) were used. Gene expression of CYP and GST, the translation initiating factor eIF4B, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…PRE herbicides play an integral role in weed control within conservation cropping systems. PRE herbicides such as imazethapyr [(Spinnaker), acetolactate synthase inhibitors], isoxaflutole [(Balance), 4-hydroxyphenyl-pyruvate dioxygenase inhibitors], S-metolachlor [(Dual Gold), cell division/ very long-chain fatty acid inhibitors], pendimethalin [(Rifle), microtubule assembly inhibitors] and prosulfocarb + metolachlor [(Boxer Gold), inhibitors of lipid synthesis and cell division/ very long-chain fatty acid inhibitors] are recommended for the control of grass weeds such as E. colona and C. virgata in many summer crops [14][15][16][17][18][19]. In this study, herbicides with different water solubility (mg/L at 20˚C) [pendimethalin (0.33), isoxaflutole (6), prosulfocarb + metolachlor (16), metolachlor (480), and while metolachlor (200), isoxaflutole (145) and imazethapyr (1.4-173) tend to highly move with soil water [20].…”
Section: Introductionmentioning
confidence: 99%
“…PRE herbicides play an integral role in weed control within conservation cropping systems. PRE herbicides such as imazethapyr [(Spinnaker), acetolactate synthase inhibitors], isoxaflutole [(Balance), 4-hydroxyphenyl-pyruvate dioxygenase inhibitors], S-metolachlor [(Dual Gold), cell division/ very long-chain fatty acid inhibitors], pendimethalin [(Rifle), microtubule assembly inhibitors] and prosulfocarb + metolachlor [(Boxer Gold), inhibitors of lipid synthesis and cell division/ very long-chain fatty acid inhibitors] are recommended for the control of grass weeds such as E. colona and C. virgata in many summer crops [14][15][16][17][18][19]. In this study, herbicides with different water solubility (mg/L at 20˚C) [pendimethalin (0.33), isoxaflutole (6), prosulfocarb + metolachlor (16), metolachlor (480), and while metolachlor (200), isoxaflutole (145) and imazethapyr (1.4-173) tend to highly move with soil water [20].…”
Section: Introductionmentioning
confidence: 99%
“…Eight reference genes (Rubisco, Actin, 18S, CAP, Tubuline, GAPDH, EF1 and Ubiquitine) chosen among those previously tested on Echinochloa spp. [28] were tested on the cDNA of two populations (161S and 45R). Serial dilutions of cDNA template (1:100, 1:50, 1:25 and 1:6.25) were tested to set up the appropriate experimental conditions.…”
Section: Relative Expression Of Als Gene Copiesmentioning
confidence: 99%
“…It is possible that other CytP450 genes are involved, which are not included in the selection of primary target genes. Dalazen et al [80] demonstrated the importance of degradation enhancement for resistance of Echinochloa crus-galli to imazethapyr in terms of relatively high expression of CYP81A6 and GSTF1 genes. Wright et al [59] studying a biotype of junglerice with resistance to four herbicides (imazamox, fenoxaprop-P-ethyl, quinclorac and propanil) demonstrated that for two of these herbicides (imazamox and quinclorac) the resistance was reduced when the herbicide was applied with a cytochrome P450 inhibitor (malathion).…”
Section: Gene Expression Profile Reflects the Transgenerational Reduces Susceptibility Memorymentioning
confidence: 99%